Peran Komunikasi Dan Pelayanan Dalam Meningkatkan Kepuasan Masyarakat - Nurbiya Tengkeran; Moh. Afan Suyanto; Deby R. Karundeng (Pusdikra Publishing, 2023)
The purpose of this research is to analyze the influence of communication and services on community satisfaction (study at the Office of Population Control, Family Planning, Women's Empowerment and Child Protection in Boalemo Regency). The data used in this study is primary data sourced from filling out questionnaires. The research population is 75 respondents using the incidental method. The analytical technique used to answer research problems and test hypotheses is multiple linear regression analysis. The results showed that communication had a positive and significant effect on community satisfaction, service had a positive and significant effect on community satisfaction and simultaneously the variables of communication and service had a positive and significant effect on community satisfaction.